GENERATING OF ELECTRIC POWER WITH THE HELP OF ELECTRET STRUCTURES - V. A. Sichik; O. A. Ermakova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers properties of electrets and electret structures. The developed method of electric power synthesis on the basis of electret structures is given in the paper. This method makes it possible to obtain significant values of current and capacity in the output circuit.